Digital Transformation : The Influence of Leadership and Organizational Culture on Business Performance through Process Innovation (International Forum of Researchers and Lecturers, 2025)
Digital transformation is no longer an option but a necessity for organizations operating in an increasingly complex and technology-driven environment. Rapid changes in market demands, technological advancements, and global competition require companies to adapt strategically to remain competitive. In this context, digital leadership and organizational culture emerge as two interrelated factors that significantly influence the success of process innovation and, consequently, business performance. This study aims to explore the relationship between digital leadership, organizational culture, process innovation, and business performance through a narrative literature review approach. The findings indicate that effective digital leadership, characterized by visionary thinking, adaptability, and a strong orientation toward technology, fosters an organizational environment conducive to creativity and change. Meanwhile, a collaborative and change-oriented organizational culture acts as a catalyst, accelerating digital transformation and improving operational efficiency. Process innovation serves as a critical intermediary that bridges leadership and culture with measurable business outcomes by enabling continuous improvement and responsiveness to market dynamics. The synergy between digital leadership and organizational culture is shown to enhance the quality and speed of innovation processes, directly impacting productivity, customer satisfaction, and financial performance. The theoretical implications highlight the importance of integrating leadership strategies with cultural transformation, while the practical implications suggest that organizations should invest in leadership development, cultural alignment, and innovation management. This study contributes to the growing body of literature on digital transformation by emphasizing the interconnected nature of leadership, culture, and innovation in driving sustainable performance improvements.